2000
DOI: 10.1002/(sici)1096-8652(200005)64:1<39::aid-ajh7>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Genetic epidemiology of HbS in Oman: Multicentric origin for the β S gene

Abstract: On the basis of a sample of 117 chromosomes, we have demonstrated the multicentric origin of the sickle mutation in Northern Oman. Three major haplotypes coexist: 52.1% Benin (typical and atypicals), 26.7% Arab-India, and 21.4% Bantu. These haplotypes are not autochthonous to Oman but originated elsewhere and arrived in Oman by gene flow. The distribution of haplotypes is in excellent agreement with the historical record, which establishes clear ancient contacts between Oman and sub-Sahara west Africa and expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Table 6 shows the distribution of the three major haplotypes in various Arab countries and clearly shows that in the Eastern Arabian Peninsula, the Arab Indian haplotype is most frequent, while among other Arab countries in Eastern Mediterranean and North Africa, the Benin haplotype predominates. This distribution is probably best explained by the supposed origin of the sickle cell mutation, with the Arab-Indian mutation originating in the Indus valley on the Indian subcontinent and subsequently spreading to Iran and Eastern Arabian Peninsula through trade routes and historical interactions (Daar et al 2000;Rahgozar et al 2000). The Benin haplotype on the other hand, has originated in Central West Africa and then spread vertically via population movement by trans-Saharan migration to North Africa and thence across the Mediterranean Sea to Bahrain Among 97 α-thalassemia chromosomes, the most common was the (α poly A1 α) (53 %), followed by (− α )and 4.2 % were undetermined (Haider and Adekile 2005) Of the 30 chromosomes from 15 patients with HbH disease, 86.7 % carried the (α polyA1 α), 10 % had (−α 3.7…”
Section: The Spectrum Of α-Thalassemia Mutations In Arab Countriesmentioning
confidence: 99%
“…Table 6 shows the distribution of the three major haplotypes in various Arab countries and clearly shows that in the Eastern Arabian Peninsula, the Arab Indian haplotype is most frequent, while among other Arab countries in Eastern Mediterranean and North Africa, the Benin haplotype predominates. This distribution is probably best explained by the supposed origin of the sickle cell mutation, with the Arab-Indian mutation originating in the Indus valley on the Indian subcontinent and subsequently spreading to Iran and Eastern Arabian Peninsula through trade routes and historical interactions (Daar et al 2000;Rahgozar et al 2000). The Benin haplotype on the other hand, has originated in Central West Africa and then spread vertically via population movement by trans-Saharan migration to North Africa and thence across the Mediterranean Sea to Bahrain Among 97 α-thalassemia chromosomes, the most common was the (α poly A1 α) (53 %), followed by (− α )and 4.2 % were undetermined (Haider and Adekile 2005) Of the 30 chromosomes from 15 patients with HbH disease, 86.7 % carried the (α polyA1 α), 10 % had (−α 3.7…”
Section: The Spectrum Of α-Thalassemia Mutations In Arab Countriesmentioning
confidence: 99%
“…17,18 In Daar et al, a study conducted in Oman in 2000 on 52 HbS/S individuals, it was found that the Benin/Benin haplotype was the most prevalent and twice more frequent than the Asian/Asian. 19 In the present study however, the Asian/Asian haplotype was the most prominent while Benin/Benin was the second in rank (Table 3). The reason for the higher percentages of Benin haplotype in Daar et al, might be due to a selection among patients attending the Sultan Qaboos University Hospital which are mainly from the Dhakhiliya region and based on our findings, the Benin haplotype has been observed to be present at a high rate in this region (Figure 2).…”
Section: Discussionmentioning
confidence: 42%
“…Contacts with East Africa, Zanzibar and Mombasa, explain the presence of the Benin and CAR haplotypes. 19 Muscat, being the capital, had the widest diversity of different haplotypes. This reflects more recent migrations of native people from the interior to the capital seeking for jobs and better lives.…”
Section: Gene Flowmentioning
confidence: 99%
“…The birth prevalence of infants with haemoglobin disorders was 3.5-4.7/1,000 Rajab and Patton 1999b). Around 10 % of Omani nationals are carriers of the gene for sickle cell anaemia, 2-3 % carry the gene for β-thalassaemia and 45 % are carriers of the α-thalassaemia gene (Alkindi et al 2010;White et al 1993;Daar et al 1998Daar et al , 2000. The high frequency in some areas may reflect natural selection due to advantage for survival, in the heterozygous state, against malaria and also to genetic drift in small isolated populations.…”
Section: Haemoglobinopathies and Red Cell Disordersmentioning
confidence: 99%